2005
DOI: 10.1002/anie.200463033
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Chemistry of the Hexavacant Tungstophosphate [H2P2W12O48]12− with FeIII Ions: Towards Original Structures of Increasing Size and Complexity

Abstract: Six FeIII centers are incorporated into the tungstophosphate anion [H2P2W12O48]12− upon reaction with FeCl3. The {P2W12Fe6} unit thus formed has been characterized in [H4P2W12Fe9O56(OAc)7]6− and [H56P8W48Fe28O248]28−. The latter is a supramolecular polyoxotungstate in which each of the four {P2W12Fe6} units is connected by three Fe‐O‐Fe bridges (see structure). Magnetic studies indicate strong antiferromagnetic coupling between the FeIII centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
90
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(92 citation statements)
references
References 44 publications
0
90
0
2
Order By: Relevance
“…(1) consists of two {(B-b-Si-W 9 O 33 (OH))(b-SiW 8 O 29 7 ]·36 H 2 O (2), a {g-SiW 10 (q av(Co-L-Co) = 99.18) than in 1 (q av(Co-LCo) = 92.88). Weaker ferromagnetic interactions were found in 2 than in 1, in agreement with larger Co-L-Co angles in 2.…”
Section: A C H T U N G T R E N N U N G (Oh))(b-siw 8 O 29 -A C H T U mentioning
confidence: 98%
See 2 more Smart Citations
“…(1) consists of two {(B-b-Si-W 9 O 33 (OH))(b-SiW 8 O 29 7 ]·36 H 2 O (2), a {g-SiW 10 (q av(Co-L-Co) = 99.18) than in 1 (q av(Co-LCo) = 92.88). Weaker ferromagnetic interactions were found in 2 than in 1, in agreement with larger Co-L-Co angles in 2.…”
Section: A C H T U N G T R E N N U N G (Oh))(b-siw 8 O 29 -A C H T U mentioning
confidence: 98%
“…[6] On the other hand, the in-situ reaction of multilacunary monomeric polyanions with paramagnetic cations can lead to oligomeric high-nuclearity species. This is generally achieved by acid-base condensation, [7] but supramolecular assemblies around small anions such as halides can also be effective. [8] Recently, insertion into paramagnetic polyoxometalate matrices of exogenous ligands and especially that of the azido anion [9] has shown that such polydentate ligands can also allow the assembly of magnetic polyoxometalate subunits, [10] but in addition could impose ferromagnetic interactions within the cluster.…”
Section: A C H T U N G T R E N N U N G [(A-a-siw 9 O 34 )A C H T U N mentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge, only one example of an iron-containing POM system synthesized under hydrothermal conditions, a [PW 12 O 40 ] 3À ion with a {Fe II A C H T U N G T R E N N U N G (phen) 2 A C H T U N G T R E N N U N G (H 2 O)} group, has been reported, [14] while the synthesis of iron-based POM materials has been extensively explored under normal bench conditions. These multi-iron complexes exhibit spectacular structures [3] and appealing magnetic [15] or electrochemical properties; [16] they are also interesting because of their catalytic properties, [17] including biomimetic catalysis. Indeed, POMs can be seen as rigid polydentate ligands with electron-acceptor properties similar to the active sites of natural enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…[W 6 6À ), [1] although POMs with new topological arrangements are still being discovered. [2] Lacunary polyoxotungstates act as ligands that can bind to 3d transition-metal ions giving rise to species containing transition-metal clusters with nuclearities from 1 to 28 [3] and exhibiting appealing properties particularly in the fields of molecular magnetism [4] and catalysis. [5] Furthermore, the incorporation of exogeneous ligands bridging the paramagnetic centers allows the magnetic coupling between the transition-metal ions encapsulated within the POM to be modulated.…”
Section: Introductionmentioning
confidence: 99%